Discharge against medical advice in culturally and linguistically diverse Australian children. Issue 12 (22nd June 2019) - Guo, Xin Yue; Woolfenden, Susan; McDonald, Gordon; Saavedra, Aldo; Lingam, Raghu
Abstract : Objectives: This study quantifies the prevalence and rates of discharge against medical advice (DAMA) in culturally and linguistically diverse (CALD) children and assesses the independent association between CALD status and DAMA accounting for key demographic confounders in a large tertiary Australian hospital network. Methods: Prospectively collected data between 2010 and 2018 were extracted from the hospital network electronic medical records system for admitted patients (n=192 037), outpatients (n=268 904) and between 2015 and 2018 for emergency department (ED) patients (n=158 903). CALD status was defined as 'preferred language being not English' and DAMA was measured as 'discharge at own risk' in admissions, 'no show' in outpatients, 'left without being seen' and 'did not wait' in ED. Data were analysed using χ² test, bivariate analysis and multivariate logistic regression. Results: The prevalence of DAMA was 1.34% in admitted patients, 19.31% in outpatients and 12.64% in ED patients. Rates of DAMA were higher among CALD children compared to non-CALD children (1.75% vs 1.29% in admitted patients, 26.53% vs 17.92% in outpatients and 18.74% vs 11.61% in ED patients). CALD status was independently associated with DAMA in admitted children (OR=1.30, 95% CI 1.15 to 1.44), outpatients (OR=1.55; 95% CI 1.51 to 1.58) and ED patients (OR=1.60; 95% CI 1.53 to 1.66). Conclusion: Being from a CALD background places children at increased risks to DAMA. Implementing appropriate health service responses may ensure equitable access and quality care for children from CALD backgrounds to reduce the rates of DAMA and its associated ramifications.